All kinds of friends, even green! - Senisi Ellen B (Bethesda, MD : Woodbine House, 2002)
In a school assignment, seven-year-old Moses, who has spina bifida and uses a wheelchair, reflects that his neighbor's disabled iguana resembles him because they both have figured out how to get where they want to be in different ways than those around them.
Keywords: Spina bifida -- Fiction; People with disabilities -- Fiction; Wheelchairs -- Fiction; Iguanas -- Fiction; Schools -- Fiction